ANALISIS HARGA POKOK PRODUKSI VIRGIN COCONUT OIL - Budianti, Dira Ayu; Nurwidianto, Nurwidianto; Saptomo, Yulius Heri (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2025)
This study aims to find out the determination of the cost of goods manufactured of virgin coconut oil according to business actors, variable costing method and full costing method and to find out the comparison of determining the cost of goods manufactured of virgin coconut oil. This type of research uses quantitative research with descriptive methods. The research subjects are five business actors and the object of research is how the comparison of determining the cost of goods manufactured of virgin coconut oil. The types of data used are primary data and secondary data. Data collection techniques are observation, interviews and documents. The data analysis method is descriptive comparative. The result showed that the determination of the cost of goods manufactured of virgin coconut oil by business actors has not been detailed and has not covered all the production costs, while the variable costing and full costing methods have covered all production costs. Comparison of the determination of the cost of goods manufactured by business actors with variable costing and full costing resulted in a very large difference while the comparison of variable costing with the full costing resulted in a small difference.